Dielectric verification of FR4 substrate using microstrip bandstop resonator and CAE tool - Hock G.C.; Chakrabarty C.K.; Emilliano; Badjian M.H. (2023)
This paper describes a method to determine the dielectric constant of FR4 substrate material at the operating frequency of 2.3 GHz. The method make used of computer aided engineering (CAE) tool and microstrip bandstop resonator for investigating the dielectric value of a material. In accordance with the data sheet provided by manufacturer which is 4.5 at 10 MHz, a set of preliminary dielectric values are selected in order to explain the proposed technique. Microstrip bandstop resonators with different dimension are designed and analyzed with the electromagnetic simulator. They are fabricated using conventional wet-etching process which is relatively economical compared to other method. After that, the actual responses of the square ring resonators are measured with the vector network analyzer. By matching up the simulation results to the measured results, dielectric values selected earlier are tuned accordingly. The obtained values are used to validate the accuracy of the proposed method. The method is simple to practice. It provides the beginners a fast way and relatively straightforward method in investigating FR4 materials for their research and learning. 2009 IEEE.